Dampak Pergantian Kurikulum 2013 dengan Kurikulum Merdeka Terhadap Motivasi Mengajar Guru Pendidikan Agama Islam dan Budi Pekerti (PAIBP) di SDN 198 Mekar Jaya Kota Bandung - Ilyas M Zakia; Siti Aisyah Nurfadillah; Muhammad Rizal; Hani Hadiati Pujawardani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research is motivated by the phenomenon of curriculum change from the 2013 curriculum to the Merdeka curriculum which affects various aspects of teacher activities in teaching, especially on teaching motivation. Teachers need quite a long time to adapt to the new curriculum. This study aims to determine the impact of the change from the 2013 Curriculum to the Merdeka Curriculum on the teaching motivation of Islamic Religious Education and Character Education (PAIBP) teachers at SDN 198 Mekar Jaya, Bandung City. Curriculum change is a strategic effort to improve the quality of national education, but in practice it poses various challenges for teachers, especially in terms of adapting to approaches and teaching tools that are different from descriptive methods. This study uses a qualitative approach. Data collection techniques use observation interviews and documentation studies. The results of the study indicate that in general, the curriculum change does not significantly reduce the teaching motivation of PAIBP teachers, even encouraging them to be more active in seeking information. However, several obstacles were found, such as lack of training, limited facilities, and a low understanding of the concepts and techniques of the Merdeka Curriculum, especially in the preparation of lesson plans and authentic assessments. The shift to a more flexible and student-centered learning paradigm requires greater teacher competence and creativity. Therefore, ongoing support in the form of training, infrastructure, and access to technology is necessary to ensure optimal implementation of the Independent Curriculum and a positive impact on the learning process.